Navigating cultural in-betweenness: A qualitative study of identity reconstruction among transnational returnees in Southeast Asia - Mohammad Naufal Firdaus; ARIO JODI FITRIAN; DIMAS RAZAN PUTRA WIJAYA; GHAZYAN AHMADINEJAD; M. SYAHRUL MAFAZA; MAHATHIR ABITAH ZUBEIR (Universitas Negeri Surabaya, 2026)
Transnational mobility has become an increasingly defining feature of contemporary higher education and professional life, yet the identity experiences of individuals who traverse multiple national and cultural contexts remain insufficiently understood, particularly within the Southeast Asian region. This study examines how transnational educational mobility shapes identity formation among individuals who have crossed national borders for education and subsequently returned to their country of origin or professional base. Using a qualitative phenomenological approach, in-depth semi-structured interviews were conducted with four participants: two Indonesian nationals who completed their education in Indonesia before relocating to work in Singapore, and two Indonesian academics who pursued postgraduate education abroad before returning to teaching positions in Indonesia. Drawing on the Transnational-Transcultural Self-Formation and Belonging (TTSB) framework, thematic analysis identified four primary themes: (1) identity negotiation between dual cultural affiliations, (2) linguistic challenges and their relationship to belonging, (3) professional identity transformation following return, and (4) adaptive strategies for cultural identity reconstruction. Findings suggest that returnees consistently inhabit an